Sexual Dimorphism Impact on the Ground Reaction Force Acting on the Mediolateral Direction During Level Walking: Hip Abductor Muscle Biomechanics and Its Correlation to GRF Moment Arm - Abd-Eltawab, Amany E.; Ameer, Mariam A.; Eladl, Mohamed Ahmed; El-Sherbiny, Mohamed; Ebrahim, Hasnaa Ali; Elsherbini, Dalia Mahmoud Abdelmonem (Frontiers in Bioengineering and Biotechnology, 2022)
The female pelvis morphology represents an evolved compensation between two opposing needs: a broad pelvis enough to deliver a sizeable brained offspring while remaining narrow enough to allow for effective bipedal gait. The precise expectation of hip abductor force generation is critical in anthropological studies & experimental practice of human stride mechanics. Hip implants and surgical procedures for hip anatomy reconstruction are based on the static single-leg stance paradigm. The current work investigated the impact of sexual dimorphism on the ground reaction force (GRF) acting on the medio-lateral direction during level walking emphasizing the difference in hip abductor muscles biomechanics and its correlation to ground reaction force moment arm, R,. The ground reaction force was measured in the medio-lateral direction, hip abduction and adduction moments during the gait cycle and ground reaction force moment arm, R,. Moreover, the kinematic parameters of angular displacement of hip abduction and adduction angle were also measured. The current study concludes that the males exhibit significantly higher mass-specific medio-lateral ground reaction force during level walking. In contrast, hip abductor moments/kg bodyweight, medialization of the trochanter, R, and hip coronal were more significant in females. We conclude that increased abductor moment and medialization of greater trochanter will increase R, hip coronal and decrease abductor moment arm, r, in females affecting the effective mechanical advantage (EMA) of hip abductors in single-limb stance during level walking.